Calculus for business, economics, life sciences and social sciences - Barnett, Raymond A. (Pearson Education, 2011)
This text covers calculus with an emphasis on cross-discipline principles and practices. It develops a thorough, functional understanding of mathematical concepts in preparation for their application in other areas.